Inflation and the rich after the global financial crisis - Branimir Jovanovic (Luxembourg Income Study (LIS), 2014)
This paper investigated the link between inflation and the top decile income share after the global financial crisis. The analysis was done on a sample of 42 countries. We found that higher inflation has reduced the income going to the top decile. The main explanation is that inflation has eroded their labour income, differently from the low-income individuals, which has been protected by minimum-wage increases. These findings imply that minimum wages should rise during inflationary episodes in order to prevent rising income inequality.
Keywords: D31; E31; G01; 330; inflation; inequality; income distribution; top income share; financial crisis; Great Recession